Caenorhabditis elegans, a Host to Investigate the Probiotic Properties of Beneficial Microorganisms - Poupet, Cyril; Chassard, Christophe; Nivoliez, Adrien; Bornes, Stéphanie (Frontiers in Nutrition, 2020)
Caenorhabditis elegans, a non-parasitic nematode emerges as a relevant and powerful candidate as a model for high-throughput studies. Experiments have demonstrated the probiotic potential of bacteria since they are capable of providing to the worm a longer lifespan, an increased resistance to pathogens and to oxidative or heat stresses. Probiotics are used to prevent or treat microbiota dysbiosis and associated pathologies. Although they are still unknown, the characterization of molecular mechanisms becomes a necessity. Beyond safety aspects of probiotics, C. elegans represents a powerful way to design large-scale studies to explore transkingdom interactions and to solve questioning about the molecular aspect of these interactions. Future challenges and opportunities would be to validate C. elegans as an in vivo tool for high-throughput screening of microorganisms for their potential probiotic use on human health and to enlarge the panels of microorganisms studied as well as the human diseases investigated.